Modelling the Peeling Behavior of Soft Adhesives - Kinloch,AJ; mohammed,IK; Charalambides,MN (Elsevier, 2016)
Peel tests were performed on pharmaceutical drug patches which consisted of a polyester backing membrane supporting an acrylic pressure-sensitive adhesive (PSA) (without and with an anti-fungal drug present) adhered to a polyethylene substrate. Interfacial separation of the PSA from the polyethylene substrate was observed in most cases. Finite element (FE) peeling simulations were conducted which characterized the backing-membrane as an elasto-plastic power-law material, the PSA as a viscoelastic material and the interfacial properties with a cohesive zone model (CZM). The mechanical response of the backing membrane and the PSA were measured from tensile experiments while the rate-dependent cohesive zone parameters, i.e. the fracture energy and maximum stress, were measured directly from poker-chip probe tack tests. The numerical results from the CZM/FE simulations and the experimental values of the peel forces as a function of the peel angle, peel speed and PSA thickness were found to be in good agreement. Two different anti-fungal drugs were added to the PSA and the influence of the drug was investigated using contact angle measurements, tensile tests, dynamic mechanical analysis and peel tests.